Antitrust Guidelines: A Simple Operational Method for Evaluating Horizontal Mergers - Davide Dragone; Luca Lambertini; Andrea Mantovani (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2007)
We reexamine the profitability and social efficiency of horizontal mergers in a Cournot oligopoly with decreasing average costs. Assuming the merger allows for efficiency gains in production, we identify the conditions under which the merger is, respectively, profitable and socially desirable. The economic preditions of the model are contrasted with FTC guidelines, based on a simple method that allows to forecast the economic consequances of a merger in terms of ex ante observables. This comparative assessment highlights the existence of well defined parameter regions where FTC guidelines lead to systematic errors.
Keywords: 330